An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)

Computing minimum spanning forests on 1- and 2-dimensional processor arrays - Meyer auf der Heide, Friedhelm (STACS 89)

Geometry and Action-Angle Variables of Multi Soliton Systems - Fuchssteiner, Benno; Oevel, Gudrun (Rev. Math. Phys.)

A systematic approach to carrier recovery and detection of digitally phase modulated signals on fading channels - Haeb-Umbach, Reinhold; Meyr, Heinrich (IEEE Transactions on Communications)
The problem of optimal carrier recovery and detection of digitally phase modulated signals on fading channels by using a nonstructured approach is presented, i.e. no constraint is placed on the receiver structure. First, the optimal receiver is derived for digitally phase-modulated signals when transmitted over a frequency-nonselective fading channel with memory. The memory results from the fact that usually the coherence time of the channel is larger than the symbol period. Symbols adjacent in time cannot be detected independently and therefore the well-known quadratic receiver is not optimal in this case. A maximum a posteriori (MAP) detector is derived and explicitly utilizes the channel memory for carrier recovery. The derivation shows that the optimal carrier recovery is, under certain conditions, a Kalman filter. Some attractive properties of this carrier recovery unit (including the absence of hang up) are discussed. Then the error rate of several digital modulation schemes is calculated taking the performance of the filter into account. The differences in susceptibility of the modulation schemes to carrier phase jitter are specified.

Die Institutionalisierung der Mathematischen Logik in Deutschland - Peckhaus, Volker (XVIIIth International Congress of History of Science. General Theme: Science and Political Order. Wissenschaft und Staat. 1st — 9th August 1989 Hamburg — München. Abstracts)

The Pseudo-Exhaustive Test of Sequential Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE International Test Conference (ITC'89))

Plattdeutsch - ein Pflegefall?

PATTERN-INDEPENDENT FSK HETERODYNE TRANSMISSION WITH ENDLESS POLARIZATION CONTROL AND A 119 PHOTOELECTRONS BIT RECEIVER SENSITIVITY - Noé, Reinhold; RODLER, H; EBBERG, A; GAUKEL, G; AURACHER, F (FIBER AND INTEGRATED OPTICS)

POLARIZATION-INSENSITIVE, 500 MBIT/S FSK TRANSMISSION OVER 153KM BY PASSIVE POLARIZATION SWITCHING - Noé, Reinhold; GIMLETT, JL; VODHANEL, RS; TSUJI, S (ELECTRONICS LETTERS)

POLARIZATION-INSENSITIVE, 500 MBIT/S FSK TRANSMISSION OVER 153KM BY PASSIVE POLARIZATION SWITCHING - Noé, Reinhold; GIMLETT, JL; VODHANEL, RS; TSUJI, S (ELECTRONICS LETTERS)

ODICE: Object-Oriented Hardware Description in CAD Environment - Rammig, Franz Josef; Müller, Wolfgang (Proc. of the Ninth IFIP Symposium on CHDLs and their Application)

Observation of a hexagonal blue phase in systems with negative dielectric anisotropy - Heppke, G.; Jéròme, B.; Kitzerow, Heinz-Siegfried; Pieranski, P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Electrostriction of the cholesteric blue phases BPI and BPII in mixtures with positive dielectric anisotropy - Heppke, G.; Jérôme, B.; Kitzerow, Heinz-Siegfried; Pieranski, P. (Journal de Physique)

Electrostriction of BPI and BPII for blue phase systems with negative dielectric anisotropy - Heppke, G.; Jérôme, B.; Kitzerow, Heinz-Siegfried; Pieranski, P. (Journal de Physique)

Das besondere Buch: Komm, Herr, segne uns. Texte und Melodien von Dieter Trautwein und befreundeten Autoren, dazu Übertragungen von Liedern und liturgischen Gesängen aus der Ökumene von Ursula und Dieter Trautwein - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Bonhoeffer-Requiem. Eindringlich, nicht aufdringlich - Schroeter-Wittke, Harald (Kirchentag '89. Berichte und Materialien aus Berlin.)

Abenteuer Kirchentag. Henning Schröer und Harald Schroeter im Gespräch mit Helmut Simon - Schroeter-Wittke, Harald; Schröer, Henning; Simon, Helmut (gep Buchmagazin Frühjahr / Sommer)

weg oder Weg? Gedanken bei der Beschäftigung mit der Gruppe Supertramp - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

God's Love "Made Visible". Eine Weihnachtsmusik von Dave Brubeck - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Compactly Embedded Cartan Algebras and Invariant Cones in Lie Algebras - Hilgert, Joachim; Hofmann, K.H. (Advances Math.)

A Note on Howe's Oscillator Semigroup - Hilgert, Joachim (Ann. Inst. Fourier)

Lie Groups, Convex Cones, and Semigroups